Rotation Signatures of TESS B-type Stars: Enlarging the Sample - J. P. S. Campelo; B. L. Canto Martins; I. C. Leão; D. O. Fontinele; R. L. Gomes; Y. S. Messias; E. Janot-Pacheco; L. A. Almeida; A. C. Brito; C. E. Ferreira Lopes; J. R. De Medeiros (The Astrophysical Journal)
Massive stars are essential for the evolution and chemical enrichment of the universe, yet their structure and evolution remain poorly understood. This study aims to expand the sample of B-type stars with known rotation periods by analyzing NASA’s Transiting Exoplanet Survey Satellite (TESS) light curves (LCs). The analysis encompasses 373 B-type stars observed with 2 minute cadence LCs from TESS, employing a manifold approach that integrates three techniques: the Fast Fourier Transform, the Lomb–Scargle periodogram, and wavelet analysis. Rotational periods were identified for 14 new B-type stars in the TESS data, while periods for 16 previously studied targets were confirmed based on literature data. Among the remaining 343 stars, as a byproduct of our analysis, we have identified 36 pulsating candidates, seven with binary signatures, and 48 hot subdwarf (sdB) candidates. Integrating these three techniques offers a robust method for separating stellar rotation from other sources of variability in the LCs, such as pulsation, binarity, and sdB. Finally, the rotational periodicities identified in this study could provide valuable constraints for refining stellar evolution models, particularly those that include rotation and advancing asteroseismic analyses of massive stars.